Relationship between self-esteem and self-care agency capacity of patients with pulmonary tuberculosis in hospital Huaycán. Lima, 2015 - Suarez Rodríguez, Rocío (2019)
Objective: The objective of this study was to determine the relationship between self-esteem and self-care agencycapacity of patients with pulmonary tuberculosis from the Low Complexity Hospital “Huaycán”. Methods:Basic research, local research, non experimental, transversal, descriptive and correlational design, the samplewas 68 patients with pulmonary tuberculosis. The data collection instruments were the Rosenberg Self-EsteemScale and the Scale of assessment of self-care agency ASA (Appraisal of Self-Care Agency Scale) of Isenbergand Evers. Results: The results showed that there is significant correlation (r = 0.261, P = 0.031) as to therelationship between self-esteem and the dimensions of self-care agency, direct and significant relation wasfound social interaction dimension (r = 0.299, P = 0.013); however, no significant relative to the size of personal,activity and rest, sufficient food consumption, and promotion of personal development and operation was found.Conclusions: It is concluded that there is significant relationship between self-esteem and social interaction ofpatients with pulmonary tuberculosis in Low Complexity Hospital “Huaycán”.